Feminist Insights from Gārgī and Maitreyī in the Bṛhadāraṇyaka Upaniṣad - A Philosophical Perspective - Prahasan , Marimuthu (South Asian Journal of Social Sciences and Humanities, 2025)
The Vedic period, in Indian history, is recognized for providing significant opportunities for women’s intellectual engagement, as evidenced by the Bṛhadāraṇyaka Upaniṣad, a seminal text of the era. Within this text, the sage Yājñavalkya emerges as a paragon of enlightenment, engaging in profound dialogues with two learned women, Maitreyī and Gārgī. These dialogues serve as the most compelling evidence of women’s scholarly participation during the Vedic period. Maitreyī, as Yājñavalkya’s wife, and Gārgī, as a philosophical interlocutor, demonstrate keen intelligence and a deep commitment to exploring the nature of the self and Brahman. This study, which adopts a feminist analytical framework, highlights the theoretical contributions made by these women within the predominantly male philosophical milieu of the time. By examining their dialogues, this research seeks to illuminate how Maitreyī and Gārgī’s intellectual pursuits shaped the metaphysical and ethical discourse of the Upaniṣads. Furthermore, their efforts to assert their scholarly presence amidst structural constraints offer insights into the women’s intellectual tradition in ancient India. These pioneering figures not only laid the groundwork for future female scholars but also provide a psychological framework for contemporary women to navigate and challenge the structural barriers still present in society today.
Keywords: Feminism; Gārgī; Maitreyī; Bṛhadāraṇyaka Upaniṣad; Yājñavalkya